COMPARISON OF THE ACHIEVEMENTS OF SMALL TOWNS IN TERMS OF SUSTAINABLE DEVELOPMENT - Matviishyn , Yevhen (Collection of scientific papers «ΛΌГOΣ», 2022)
It is important for community residents, business entities, local government employees and other stakeholders to have comparative assessments that characterize the quality of governance. Of key importance in exploring the theme of quality governance for sustainable development is the role of government [1]. In the case of urban territorial communities, the main role is given to local governments – city councils. The use of benchmarking is well suited to assess the effectiveness governance for sustainable development of small towns. Available open data on the research objects achievements have been used, which is especially relevant in conditions of limited funds and resources for additional research to obtain analytical information. Based on the application of benchmarking, the effectiveness of governance for sustainable development of small towns in Lviv Region (Ukraine) was compared. This approach meets the requirements for the selection of objects for benchmarking research, in particular, for the similarity of their economic, demographic, geographical, and other conditions.